Guide on Resource Revenue Transparency. (Policy Papers; Policy Paper, 2005)
This guide gives a framework that covers the resource-specific issues to be considered in a fiscal transparency assessment, for example as part of a fiscal Report on the Observance of Standards and Codes (ROSCs). Equally importantly, it provides a summary overview of generally recognized good or best practices for transparency of resource revenue management that can be used by countries themselves, as well as by the IMF, the World Bank, and others providing technical support.